(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Population explosion is a major problem it is raising tremendously; this may affect drastically the economic growth. Sofamily planning has been promoted through several methods of contraception. A wide variety of synthetic contraceptiveagents are available, but these cannot be used continuously due to their side effects. Thus the present study was to evaluatethe effect of Bougainvillea spectabilis on fertility of male and female mice. Swiss Albino mice were orally administeredwith aqueous crude extract of the leaves of Bougainvillea spectabilis (800 mg/kg of body weight/day, for 30 days), andeffect of crude extract on reproductive organs and fertility was investigated. The treatment Caused decrease in weight oftestis, sperm count and the histological examination revealed a reduction in the size of seminiferous tubules along with thethickness of germinal epithelial cells, though some of the epithelial cells and interstitial cells of leydig showedhypertrophy. Moreover, the lumen of the tubules was found to be devoid of sperms. On the other hand, in treated femalesno histological changes could be observed. The only marked change, which could be visualized, was the slight disruptionof estrous cycle having prolonged metaestrus phase, which has been increased by 145.28 %. The overall duration of estrouscycle had been extended by more than one day. The hormonal profile was also influenced by the Bougainvillea spectabilisextract. The testosterone and estrogen levels were significantly decreased